Access, referral, service provision and management of individuals with primary progressive aphasia: A survey of speech‐language therapists in Italy - Battista, Petronilla; Piccininni, Marco; Montembeault, Maxime; Messina, Annachiara; Minafra, Brigida; Miller, Bruce L.; Henry, Maya L.; Gorno Tempini, Maria Luisa; Grasso, Stephanie M. (International journal of language & communication disorders, 2023)
Background and Objectives In Italy, approximately 650 individuals receive a diagnosis of primary progressive aphasia (PPA) every year. Unfortunately, the frequency with which patients are referred to speech‐language services is suboptimal, likely due to skepticism regarding the value of speech‐language therapy in the context of neurodegeneration. Materials and Methods We conducted a virtual survey of speech and language therapists (SLTs) across Italy, to collect information about the assessment, intervention and management of patients with PPA. To ensure that as many SLTs as possible received the survey, the Italian Federation of SLTs (Federazione Logopedisti Italiani, FLI) aided in disseminating the survey. Results In total, 336 respondents participated in the online survey, 140 of whom had previous experience with PPA patients. Respondents indicated having seen a total of 428 PPA patients in the previous 24 months (three patients on average, range: 0–40). SLTs who reported never working with PPA identified underdiagnoses, low referral rates and the rarity of the clinical syndrome as major reasons for their lack of experience with PPA. SLTs with experience working with PPA indicated that patients may not have accessed services because of service dysfunction and geographical barriers. Respondents reported using informal interviews during assessments and tests developed for post‐stroke aphasia, while impairment‐based/restitutive interventions were utilised most often. Conclusion Findings may serve to inform health policy organisations regarding the current shortcomings and needed recommendations for improving the care of individuals with PPA in Italy. Improving awareness of the utility of rehabilitation among SLTs and other clinical service providers may serve to facilitate access to intervention, which in turn will serve to better support individuals living with PPA. What This Paper Adds What is already known on the subject Speech and language therapists (SLTs) play a crucial role in the assessment, diagnosis and treatment of people with primary progressive aphasia (PPA). However, the frequency with which individuals with PPA are referred for speech and language services is suboptimal due to skepticism regarding the value of speech and language therapy in the context of neurodegeneration, the scarcity of SLTs with expertise in the treatment of PPA and the lack of awareness of the SLT role amongst referrers. What this paper adds to existing knowledge In recognition of the lack of published information on the provision of speech and language therapy services and clinicians’ approaches to the assessment and treatment of individuals with PPA in Italy, we conducted an online survey to evaluate the current referral patterns for speech and language therapy services and to examine the current barriers to access these services for individuals with PPA in Italy. What are the potential or actual clinical implications of this work? The data presented here support that SLTs view treatment as useful for individuals with PPA and other professional figures and may serve to improve access to intervention, which in turn will serve to better support individuals living with PPA. The results highlight the need to inform health policy organisations about current gaps and aid in developing recommendations for improving the care of individuals with PPA, in order to understand how SLTs can best support individuals with PPA and their families.